A Critical Reading of the “Educational” Neo-language of Competencies: The Case of Colombia - Cárdenas-Támara, Felipe; Choconta Bejarano, Johanna (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This study aimed to understand, from a critical point of view, the condition of semantic, discursive, and rhetorical displacement that operates in the Colombian educational system, where the category of education has been displaced by the concept of competence. The following question guides the investigation: What are the deep meanings, from semiotic considerations and discourse analysis, that underlies the rationality of competencies as a category inserted in the discourse of the Ministry of National Education of Colombia (MEN)? The research confirms that since 2004, under the neoliberal government of Álvaro Uribe Vélez, the Colombian educational system has been guided by an instrumental and economistic conception of education, whose logic is characterized by the notions of "efficiency", "competence", "results" and "success" as categories that indicate the educational horizon promoted by the Colombian State. We argue that the pragmatic result is an institutional isomorphism that tends to nullify real social participation and creates conflict, ignoring the cultural and regional diversity of the country.